Pengaruh Rekrutmen dan Pengembangan Karir Terhadap Kinerja Karyawan pada PT. Sukses Mitra Sejahtera Kabupaten Kediri - Niken Anggraini Nur Islami; Ahmad Jauhari; Nur Hidayati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study aims to examine the effect of recruitment and career development on employee performance by researchers. This study uses independent variables, namely recruitment and career development, and the dependent variable, namely employee performance. The sample in this study is monthly employees at PT. Success of Mitra Sejahtera Kediri Regency. Data were obtained through questionnaires, observations, and interviews. The sampling technique is carried out by the simple random sampling technique method. The analysis technique uses Multiple Linear Regression Analysis, with hypothesis testing of t test and F test. The results of this study show that recruitment does not have a partial effect on employee performance, it is known from the results of the sig value recruitment t test. = 0.677 > 0.05. The results of career development research show that it has a significant effect on employee performance, this is known from the results of the sig value recruitment t test. = 0.000 > 0.05. The results of recruitment and career development research have a simultaneous effect on employee performance, it is known from the F test of the sig value. = 0.000 < 0.05